FREQUENCY OF CD34 EXPRESSION IN ACUTE LYMPHOBLASTIC LEUKAEMIA AND ITS CORRELATION WITH CLINICOPATHOLOGICAL CHARACTERISTICS: A SINGLE CENTRE EXPERIENCE FROM PAKISTAN - Bashir, Zaratulain; Jawad Hassan; Samra Waheed; Mahjabeen Imam; Naveena Fatima; Sidra Zafar; Saima Siddiqui; Tahir Shamsi (Journal of Ayub Medical College Abbottabad, 2022)
Background: This study was carried out to determine the frequency of CD34 positivity in acute lymphoblastic leukaemia (B-ALL) in our population and to report its association with the clinicopathological profilet the time of diagnosis. Methods: The cross-sectional study was conducted at National Institute of Blood Diseases and Bone Marrow Transplantation, Karachi, Pakistan, from March 2020 till December 2020.Newly diagnosed patients were selected, from both genders and all age groups. Relevant history and findings of physical examination were recorded. Immunohistochemistry was done on trephine biopsy and molecular studies were carried on bone marrow aspirates or peripheral blood samples. Results: Out of 105 patients enrolled, 67(63.8%) were males, with a male to female ratio (M: F) 1.8:1. Of the total patients, 62 (59.04%) were above 15 years of age. CD34 was expressed in 73 (69.5%) cases. Lymphadenopathy, splenomegaly, and hepatomegaly were separately noted in context to CD 34 expression in 22 (66.6%), 24 (64.8%), and 14 (58.3%) patients, respectively. CNS disease was seen in a total of 3(2.75%) subjects, in which 2 (66.6%) of the patients had CD34 expression. Total 81 patients in our study fall into the high-risk group out of which CD 34 expression was seen in 58(71.6%) subjects. Cytogenetic analysis, BCR-ABL p190, and MLL gene rearrangement were investigated in all participants. Cytogenetic analysis revealed an abnormality in 20 (19%) cases out of which 13 (17.8%) cases were from CD34 positive group. Conclusion: Our study reported CD34 expression in more than two-thirds of cases. High-risk disease was significantly associated with CD34 expression.